Prevalence and Economic Significance of Cystic Echinococcosis among the Slaughtered Animals in Elazig - Kaplan, M.; Baspinar, S. (Medwell Online, 2009)
Cystic echinococcosis is a widespread zoonosis that causes disease and weakness in animals and humans and in the most serious cases, death of the host. Nowadays, it is also re-emerging as an important public health issue. This study aimed to investigate the prevalence of Cystic Echinococcosis (CE) in slaughtered butchery animals in Elazig and determine its effects on economic losses, between 2002 and 2007. The data, which obtained from the records of Provincial Directorate of Agriculture in 6 different private and public slaughterhouses in Elazig, were retrospectively investigated. The prevalence of CE in slaughtered sheep, goat and cattle during this 6 years period were found between 3.43-6.60, 0.55-2.18 and 0.94-4.16%, respectively. The CE infection was significantly higher in lung (1.87%) compared to liver (1.42%) and heart (0.06%). We calculated economic loss due to the discarded organs, which is infected with CE, as 192,457 US dollars. The amount of economic loss appears to gradually increase and CE prevalence in the butchery animals slaughtered in our province seems to have not decreased compared to the previous years despite the all official effort to prevent this infection.
Keywords: Cystic echinococcosis; sheep; goat; cattle; economic loss